Genetic loci linked to Type 1 Diabetes and Multiple Sclerosis families in Sardinia - Frongia Paola; Maioli Mario; Pacifico Adolfo; Pala Gavino; Nucaro Annalisa; Lampis Rosanna; Contu Daniela; Corongiu Daniela; Secci Maria; Rolesu Marcella; Cuccu Stefania; Tranquilli Stefania; et al. (BMC, 2008)
Abstract Background The Mediterranean island of Sardinia has a strikingly high incidence of the autoimmune disorders Type 1 Diabetes (T1D) and Multiple Sclerosis (MS). Furthermore, the two diseases tend to be co-inherited in the same individuals and in the same families. These observations suggest that some unknown autoimmunity variant with relevant effect size could be fairly common in this founder population and could be detected using linkage analysis. Methods To search for T1D and MS loci as well as any that predispose to both diseases, we performed a whole genome linkage scan, sequentially genotyping 593 microsatellite marker loci in 954 individuals distributed in 175 Sardinian families. In total, 413 patients were studied; 285 with T1D, 116 with MS and 12 with both disorders. Model-free linkage analysis was performed on the genotyped samples using the Kong and Cox logarithm of odds (LOD) score statistic. Results In T1D, aside from the HLA locus, we found four regions showing a lod-score ≥1; 1p31.1, 6q26, 10q21.2 and 22q11.22. In MS we found three regions showing a lod-score ≥1; 1q42.2, 18p11.21 and 20p12.3. In the combined T1D-MS scan for shared autoimmunity loci, four regions showed a LOD >1, including 6q26, 10q21.2, 20p12.3 and 22q11.22. When we typed more markers in these intervals we obtained suggestive evidence of linkage in the T1D scan at 10q21.2 (LOD = 2.1), in the MS scan at 1q42.2 (LOD = 2.5) and at 18p11.22 (LOD = 2.6). When all T1D and MS families were analysed jointly we obtained suggestive evidence in two regions: at 10q21.1 (LOD score = 2.3) and at 20p12.3 (LOD score = 2.5). Conclusion This suggestive evidence of linkage with T1D, MS and both diseases indicates critical chromosome intervals to be followed up in downstream association studies.